Impacts on U.S. energy expenditures and greenhouse-gas emissions of increasing renewable-energy use : technical report - Toman, Michael A. (Technical report (Rand Corporation), 2008)
"How could producing 25 percent of U.S. electricity and motor-vehicle transportation fuels from renewables by the year 2025 affect U.S. consumer energy expenditures and CO[subscript 2] emissions? This report finds that reaching 25 percent renewables with limited impact on expenditures requires significant progress in renewable-energy technologies and biomass production. Without substantial innovation in these areas, expenditures could increase considerably."--Jacket